Partisan differences and the interventionist state in advanced democracies - Schmitt, Carina; Zohlnhöfer, Reimut (Socio-economic review, 2019)
We present new evidence on whether political parties still matter in economic policy-making. We investigate four policy instruments (changes in product market regulation (PMR), subsidies, business taxation, social spending) in 21 OECD countries between 1980 and 2015. We systematically consider how cabinet duration and the challenges of globalization, the EU and economic problems (debt, unemployment, economic growth) condition partisan differences. Partisan differences only really make themselves felt after about one term in office. Moreover, with the exception of PMR, partisan differences tend to become more pronounced as globalization increases while European integration does not condition partisan effects. The conditioning effect of domestic economic problems on partisan differences depends on a policy instrument’s salience. In highly salient issue areas (social expenditure, corporate taxation), we only find partisan differences when problems are low; in contrast, economic problems emphasize partisan differences in non-salient issue areas (PMR, subsidies).
Advance access publication date: 7 December 2017
Keywords: Aufsatz in Zeitschrift